Situation of Intimate Partner Violence among University Female Students in Nepal: Findings of a Cross-Sectional Survey - Sedain, Bhagabati (Bodhi: An Interdisciplinary Journal, 2019)
Intimate partner violence (IPV) is one of the most common forms of violence in our society. Intimate partner violence among Nepali female university students, in particular, has not yet been studied. Therefore, across-sectional survey was conducted among female students studying in bachelors and masters level at Padmakanya Campus using structured and semi-structured questionnaires. A total of 370 participants were randomly selected and data were collected from the 1 December 2013 to 30 January 2014. One-thirds of the respondents were married. Married participants reported about their violence experience perpetrated by their husbands. The prevalence of emotional violence 40% was higher than physical 33% and sexual violence 20%. Women with landownership, employed, members of community groups and those who were married to husbands with the higher level of education were less likely to experience physical violence. Women who did not own land (OR=2.92), unemployed (OR=1.21) were more likely to experience violence than those who owned land and were employed. Similarly, lower level of husband's education (OR=3.35) and unskilled jobs (OR=1.56) were associated with the higher occurrence of violence compared to their husbands having university level of education and government job or working abroad. Prevalence of IPV is common among educated girls. Efforts to reduce IPV should give priority for educated women in Nepal.